2015
DOI: 10.1177/1039856215608282
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a culturally adapted training course in Indigenous e-mental health

Abstract: E-mental health is a relatively new development that may contribute to improved access to mental health services for rural and remote Indigenous Australians, particularly where such tools are culturally adapted. Whilst current knowledge and use of e-mental health tools in this group of Northern Territory service providers was limited, perceived knowledge and confidence in use was significantly improved following training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 14 publications
2
55
0
Order By: Relevance
“…Limited knowledge of e-mental health tools amongst health practitioners is a key obstacle to use. This finding accords with results from a recent eMHPrac training evaluation [ 21 ] and reports of poor implementation of e-mental health approaches across Australian health services, despite Australian developers playing a leading role in the development of e-mental health innovations internationally [ 22 ]. Similarly, a recent systematic review found that one of the key impediments to more widespread use included lack of awareness and knowledge about e-mental health amongst clients and practitioners [ 17 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Limited knowledge of e-mental health tools amongst health practitioners is a key obstacle to use. This finding accords with results from a recent eMHPrac training evaluation [ 21 ] and reports of poor implementation of e-mental health approaches across Australian health services, despite Australian developers playing a leading role in the development of e-mental health innovations internationally [ 22 ]. Similarly, a recent systematic review found that one of the key impediments to more widespread use included lack of awareness and knowledge about e-mental health amongst clients and practitioners [ 17 ].…”
Section: Discussionsupporting
confidence: 89%
“…Some have found that e-mental health approaches can be implemented successfully by practitioners with little mental health training [ 26 ]. An evaluation of a one-day e-mental health training course provided through eMHPrac has shown that participants with diverse roles and professional backgrounds improved their knowledge and skills in e-mental health significantly post-training [ 21 ]. The availability of appropriately-targeted training in e-mental health will be a crucial component of e-mental health implementation; however, workforce factors also indicate a need earlier in the development phase for production of new tools which are evidence-based, easily understood, appropriately targeted and require little training.…”
Section: Discussionmentioning
confidence: 99%
“…There were also dissimilarities in the primary cultural differences discussed across studies which justified the need for cultural competence. Some included studies discussed cultural differences as distinctions in understandings of health that exist among different population groups, for example the holistic understandings of health held by Indigenous people and how this differs from mainstream approaches to health [ 41 , 42 ]. Other studies discussed communication issues related to language discordance and cultural differences and how these affect clinical encounters, particularly for Hispanic populations in the United States [ 43 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Professional development interventions used both training and mentoring/supervision to increase the cultural competence of the health workforce. Five studies delivered training concentrated on particular health issues/fields or specific interventions [ 41 , 42 , 48 , 51 , 52 ], and four studies used mentoring/supervision strategies [ 39 , 43 , 52 , 53 ]. Mentoring and supervision strategies aimed at increasing cultural competency were employed with individual practitioners, entire health services, and minority research faculty and students.…”
Section: Resultsmentioning
confidence: 99%
“…The Stay Strong Care plan was developed and evaluated by Professor Tricia Nagel and developed into a mobile electronic app for iPads and other tablets in collaboration with Queensland University of Technology [ 19 , 20 ]. The app is a structured mental health and substance misuse intervention available through iTunes or Google Play.…”
Section: Methodsmentioning
confidence: 99%